Depressive symptoms homophily among community-dwelling older adults in japan: A social networks analysis - Ayako Morita; Yoshimitsu Takahashi; Kunihiko Takahashi; Takeo Fujiwara (Frontiers Media S.A., 2022)
Late-life depression is one of the most common mental illnesses that cause serious consequences, but the majority do not reach out for mental health services and relapses are common. The present study investigated profiled similarity of older adults' social networks in terms of depressive symptoms. In 2017, we distributed questionnaires inquiring about confidants in the community, depressive symptoms based on the 15-item Geriatric Depression Scale (GDS-15), and demographic and functional characteristics to all the community-dwelling older adults under the national insurance system in Wakuya City (Miyagi prefecture, Japan). Applying the Exponential Random Graph Model, we estimated the likelihood of a confidant relational tie by the similarity of overall and specific depressive symptoms within 217,470 potential ties among 660 respondents eligible for analysis. The overall depressive symptom homophily was marginally significant (p < 0.10), indicating that the likelihood of a confidant relational tie between two community-dwelling older adults was decreased by 5%, with one point increase in their difference in the total number of depressive symptoms (odds ratio [OR], 0.95; 95% confidence interval [CI], 0.90-1). Focusing on specific domains of depressive symptoms, we found significant apathy homophily (p < 0.05) but no significant suicidal ideation of homophily. The results indicated that there is a 19% decrease in the likelihood of a confidant relational tie between two community-dwelling older adults by one point increase in their difference in the total number of apathy symptoms (OR, 0.81; 95%CI, 0.67-0.98) but no change by increasing the difference in their total number of suicidal ideation symptoms (OR, 1; 95%CI, 0.87-1.14). These findings suggest depressive symptom homophily, particularly with respect to apathy domains, in confidant social networks of community-dwelling older adults, and the importance of network intervention in preventing late-life depression.